Protective effect of antilipopolysaccharide monoclonal antibody in experimental Klebsiella infection. - Rukavina, T (1997)
An O-antigen-specific murine monoclonal antibody (MAb) directed against an immunodominant epitope expressed on Klebsiella O1, O6, and O8 lipopolysaccharides (LPS) was examined with respect to its binding to nonencapsulated and encapsulated bacterial cells and its ability to protect against lethal murine Klebsiella sepsis. While the MAb (clone Ru-O1, mouse immunoglobulin G2b) bound well to nonencapsulated organisms of the O1 serogroup, binding was significantly, but not completely, abolished by the presence of the K2 capsule. In a model of experimental Klebsiella peritonitis and sepsis induced by a virulent O1:K2 serogroup strain, higher doses of anti-LPS MAb Ru-O1 than of a previously described anticapsular MAb specific for the K2 capsular polysaccharide were needed to provide protection. However, high-dose (40 microg/g of body weight) pretreatment with anti-LPS MAb Ru-O1 significantly reduced bacterial dissemination to various organs as well as macroscopic and histologic pulmonary alterations. Thus, since the number of Klebsiella capsular antigens occurring in clinical material is too large to be completely "covered" by a K-antigen-specific hyperimmunoglobulin preparation, O-antigen-specific antibodies may supplement K-antigen-specific immunoprophylaxis and -therapy of clinical Klebsiella infection.